THE AGE RELATIONSHIP AND TYPES OF WORK WITH ASI PRODUCTION REGIONAL PUSKESMAS PUBLIC WORK AREA BOGOR: HUBUNGAN UMUR DAN JENIS PEKERJAAN DENGAN PRODUKSI ASI DI WILAYAH KERJA PUSKESMAS PASIR MULYA BOGOR - Triswanti Triswanti (Jurnal Ilmiah Wijaya, 2019)
Indonesian demographic and health survey data (SDKI) in 2016 show that as many as 48'4% of infants in Indonesia receive exclusive breastfeeding at the age of 4-5 months.whereas based on a report from the provincial health office in 2015, the number of exclusive breastfeeding is usually given to infants aged 0-6 months, only reaching 44.1%.relatively few figures, even though breastfeeding and breastfeeding both mother and baby will get many benefits.even this will have an impact on the environment, society, nation and state.3 know the combination of age and type of work with ASI production in the work area of the Pasir Mulya community health center in 2018. This type of research is analytic with cross sectional design. The method of taking samples in this study is total sampling with a sample of 99 people.the instruments used were questionnaires and observation sheets while the data analysis techniques used univariate, bivariate and multivariate Analysis. based on the age of the mother it is known that 53 (53.5%) of the mother's age is not at risk with sufficient milk production and 12 (12.1%) of mothers at risk of adequate milk production, and from maternal work it is known that 50 (50.5%) mothers do not work with sufficient milk production and 15 (15.1%) mothers work with sufficient milk production. From the results of multivariate analysis, it was found that the type of work had more influence on the production of breast milk with P value 0.002 compared to the age of the mother with p value 0.010.so that mothers who do not work will be more sufficient for their ASI production compared to working mothers,because mothers who don't work have more time spent with their children. they can see the child's development, and vice versa. and the statistical test value show p-value (0'000) and α = 0.01 it can be concluded that ha is accepted ho is rejected and it shows there is a relationship between age and type of work with ASI production in Pasir Mulya community health center in 2018.